RESPONSIBILITY AND LEGAL PROTECTION OF NOTARY AGAINST PARTIJ ACTE - Rachman, Rahmia; Yustisia Lestari, Titie; Amin Tahir, Maulana (fakultas hukum universitas PGRI Semarang, 2025)
Notaries are responsible for complying with laws and regulations in terms of carrying out their official duties, therefore based on the great responsibility of notaries, especially in making partij acte which is directly related to the interests of the faces, notaries need to get legal protection. The purpose of this research is to find out the legal responsibility for notaries in making partij acte and to find out the legal protection for notaries in making partij acte. This research uses normative legal research methods. The results show that there are 3 (three) forms of legal responsibility for notaries in making partij acte, namely administrative responsibility, civil responsibility and criminal responsibility. Legal protection for Notaries is institutionally provided by the Notary Honor Council and by law Notaries receive legal protection through the obligations / rights of Notaries.